Crime and victimisation in people with intellectual disability: a case linkage study. Issue 1 (December 2016) - Fogden, Billy; Thomas, Stuart; Daffern, Michael; Ogloff, James
Abstract Background Studies have suggested that people with intellectual disability are disproportionately involved in crime both as perpetrators and victims. Method A case linkage design used three Australian contact-level databases, from disability services, public mental health services and police records. Rates of contact, and official records of victimisation and criminal charges were compared to those in a community sample without intellectual disability. Results Although people with intellectual disability were significantly less likely to have an official record of victimisation and offending overall, their rates of violent and sexual victimisation and offending were significantly higher. The presence of comorbid mental illness considerably increased the likelihood of victimisation and offending; several sex differences were also noted. Conclusions People with intellectual disability are at increased risk for both violent and sexual victimisation and offending. The presence of comorbid mental illness aggravates the risk of offending and victimisation. Future research should focus on a more nuanced exploration of the risks associated with intellectual disability and specific mental disorders and related indices of complexity.